9(t-5)+5t=7(2t+5)-13

Simple and best practice solution for 9(t-5)+5t=7(2t+5)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(t-5)+5t=7(2t+5)-13 equation:


Simplifying
9(t + -5) + 5t = 7(2t + 5) + -13

Reorder the terms:
9(-5 + t) + 5t = 7(2t + 5) + -13
(-5 * 9 + t * 9) + 5t = 7(2t + 5) + -13
(-45 + 9t) + 5t = 7(2t + 5) + -13

Combine like terms: 9t + 5t = 14t
-45 + 14t = 7(2t + 5) + -13

Reorder the terms:
-45 + 14t = 7(5 + 2t) + -13
-45 + 14t = (5 * 7 + 2t * 7) + -13
-45 + 14t = (35 + 14t) + -13

Reorder the terms:
-45 + 14t = 35 + -13 + 14t

Combine like terms: 35 + -13 = 22
-45 + 14t = 22 + 14t

Add '-14t' to each side of the equation.
-45 + 14t + -14t = 22 + 14t + -14t

Combine like terms: 14t + -14t = 0
-45 + 0 = 22 + 14t + -14t
-45 = 22 + 14t + -14t

Combine like terms: 14t + -14t = 0
-45 = 22 + 0
-45 = 22

Solving
-45 = 22

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| g/3+5=4 | | 3-27/2= | | 4x-2=-3+5x | | y/2-1=5 | | -2+5=-9 | | g+(-4)=12 | | -5+s=8 | | v-12=-4 | | (2x+1)=2 | | 2(a-8)+7=5(a-2)-4a-19 | | z^2+18z+62=0 | | z^2+182+62=0 | | (X^3-13x+12)/(x-3) | | -5/8y=-5 | | 9(x+3)=3(x+3) | | 1-4n=-n-2 | | x+5forx=-18 | | 4a-5b= | | 49Z+4=54 | | 7y^0= | | (6^3/9)+(18+10)^2 | | 14/5(3/10) | | K=13+5k | | -3=-2/3+v/3 | | 33+17=x-20 | | 8+10y+3y-12= | | -3=-2+v | | 441=x^2+20x | | 0=-1+n/10 | | 100x^2-1=99 | | 28=3n-2 | | 9k+8= |

Equations solver categories